Game Science: Foundations and Perspectives. (June 2018) - Kriz, Willy C.; Harviainen, J. Tuomas; Clapper, Timothy C.
Background. Game studies offer cross-disciplinary perspectives, but the body of knowledge is not yet in the form of a cohesivegame science paradigm. Klabbers (2018a) argues that a comprehensive and coherent view on game science is needed that connects three levels of inquiry: thephilosophy of science level, thescience level, and theapplication level . Aim. This single-theme symposium issue On the Architecture of Game Science is especially devoted to the reflection and discussion on the foundations and principles ofgaming and simulation . Method. Raising a debate among scholars and professionals, addressing the questions and frame-of-reference presented in the introductory article of Klabbers (2018a) and completed by his rebuttal. Results. The contributions range from the linkages between game science andcomplex social systems design through gaming simulation, togamification science, andgame studies, focusing on theludosphere and the growing field ofdigital games . Conclusion. The articles present an overview of the currentstate of the art, craft, and science of gaming simulation, gamification and game studies. They present a stimulating and challenging debate, and a good basis for advancing the principles and foundations of game science.